Paradise Lost: Value Formations as an Analytical Concept for the Study of Gamevironments - Grieve, Gregory Price (Gamevironments, 2020)
This article argues that researchers of religion and video gaming, including but not limited to gamevironments, should now leave their initial use of the category of religion behind. While religion might work for interpreting explicit religious elements in the content of a video game, it misses the majority of underlying or implicit religious topics within the game and gameplay as well as the surrounding media platforms. We argue that value formations rather than religion, is a better analytic category to understand how gamevironments generate meaning and reflect or undermine broader social and cultural discourses and how this is connected to religion. Value formation indicates the collections and systematization of interdependent and entangled values, which are the production, product, and reproduction of values. Our concept of value formations derives from a social-constructivist approach, which understands values not as timeless, essential, universal or static, but rather as constructed by specific social locations. Values are therefore discourses and practices that are constantly (re)defined and (re)negotiated by competing actors according to time, context, and skill. These actors can be individual persons, groups, or organizations. In contrast to a normative or critical perspective, our goal is not to evaluate these values, but rather analyze how the different individual and collective actors (re)define and understand something as value. To support our argument, this article analyses three case studies. First, we describe our case study, the gamevironments of Far Cry 5’s mission Paradise Lost (2018). Second, we offer a theory of value formations, which gives a working definition, a short genealogy, as well as relates value to the concepts of ethics, aesthetics, and norms. Third, we put these to work by investigating value formations in Far Cry 5’s gamevironments, which include both its gameplay as well as peripheral media platforms. We conclude by outlining how the concept of value formations adds to the study of video games overall and gamevironments particularly